Metropolis : [videorecording (DVD)] : the splendor of cities throughout the ages (Koch Vision, 2008)
Go into the very heart of ancient and medieval urban life to examine the crucial and historic steps towards civilization, in cities such as Athens, Carthage, Rome, Venice, Paris, and many more.